A Comprehensive Study of Pharmacologic Complexity: Study of Interactions and Properties of Paracetamol, Aspirin, Naproxen, and Diclofenac - Azeez , Yousif; Omer , Rebaz; Othman , Khdir; Omar, Karzan A.; Qader, Aryan (Orbital: The Electronic Journal of Chemistry, 2025)
The present study explores the molecular and electronic properties of four widely used pharmaceutical compounds—Paracetamol, Aspirin, Naproxen, and Diclofenac—to enhance our understanding of their stability, reactivity, and potential applications in drug design. Through computational analysis, key electronic properties and intermolecular interactions were examined to reveal factors influencing their chemical behavior. Using density functional theory (DFT) with the B3LYP/6-31G(d,p) level, the study investigates their electronic structure, charge distribution, and optical characteristics. Reduced Density Gradient (RDG) and Non-Covalent Interaction (NCI) analyses highlight distinct intermolecular interactions, such as strong hydrogen bonding in Paracetamol, π→π* transition stabilization in Aspirin, dispersion interactions in Naproxen, and diverse attractive forces in Diclofenac. Natural Bond Orbital (NBO) analysis further elucidates electron delocalization effects. The study also evaluates Nonlinear Optical (NLO) properties, suggesting potential applications beyond pharmaceuticals. Quantum chemical parameters indicate that Aspirin has the highest ionization energy (10.18 eV), making it a strong electron acceptor, while Paracetamol demonstrates significant electron-donating ability. Molecular Electrostatic Potential (MEP) mapping provides insights into charge distribution and reactivity, while UV-Visible absorption spectra reveal optical characteristics relevant to various applications. These findings offer valuable insights into the fundamental electronic behavior of these pharmaceutical compounds, which may inform drug formulation, bioavailability studies, and potential modifications for enhanced therapeutic efficacy. By linking computational analysis with pharmaceutical applications, this study contributes to a deeper understanding of molecular interactions that govern drug stability and performance.